Grape pomace as a sustainable source of bioactive compounds : extraction, characterization and biotechnological applications of phenolics - Fontana, Ariel Ramón (2013)
Grape pomaces (GP) are characterized by high contents of phenolics due to an incomplete extraction during winemaking process. These phenolics are secondary plant metabolites with potential beneficial effects on human health because of their antioxidant activity and antimicrobial, antiviral and anti-inflammatory properties. Therefore, GP constitutes an inexpensive source for the extraction of phytochemicals that can be used in pharmaceutical, cosmetic and food industries. As a result of the increased attention to sustainability of agricultural practices, efforts have been made to use GP in different fields of industry. Thus, it is necessary to have efficient extraction techniques to achieve good recoveries of compounds. On this respect, sensitive and selective analytical methods have been tried for the characterization of phenolics extracts. This review summarizes the most recent developments in extraction of polyphenols from GP. Furthermore, the techniques used for characterization of extracts are explained, with emphasis in sample preparation, separation and analysis of phenolics. Finally, the possible applications of GP extracts in diverse biotechnological fields are also discussed.